Negative Emissions: Priorities for Research and Policy Design - Fajardy, Mathilde; Patrizio, Piera; Daggash, Habiba Ahut; Mac Dowell, Niall (Frontiers in Climate, 2019)
The large-scale removal of carbon dioxide from the atmosphere is likely to be important in maintaining temperature rise “well below” 2ºC, and vital in achieving the most stringent 1.5ºC target. Whilst various literature efforts have estimated the global potential of carbon dioxide removal (CDR) for a range of technologies with different degrees of certainty, regional bottlenecks for their deployment remain largely overlooked. Quantifying these barriers, through national and local case studies, rather than with aggregated approaches, would guide policy and research, as well as investments, towards regions that are likely to play a prominent role in CDR deployment. Five CDR technologies – including afforestation/reforestation, bioenergy with carbon capture and Storage, biochar, direct air capture and enhanced weathering – are compared in this work. We discuss main technical, socio-economic and regulatory bottlenecks that have been scarcely investigated at regional level, and provide directions for further research. We identify the availability of accessible land, water, low carbon energy and CO2 storage as key regional drivers and bottlenecks to most CDR technologies. We discuss the caveats in CO2 accounting in assessing the performance of each technology, and the need for an international regulatory framework which captures these differences. Finally, we highlight the social, economic and political drivers which are central in unlocking the large scale deployment of CDR technologies, in a cost attractive, socially acceptable and politically achievable way.